Kemampuan Berpikir Komputasional Matematis Ditinjau dari Self Efficacy Siswa Kelas VIII SMPN 226 Jakarta - Siti Haniifah; Esti Ambar Nugraheni (Pendidikan Matematika Universitas PGRI Yogyakarta, 2024)
Computational thinking ability is the ability to solve complex problems with algorithmic solutions based on computational aspects. Self efficacy is a belief in one's own abilities. The subjects in this study are class VIII-H students at SMPN 226 Jakarta as many as 34 students who will then be selected 3 students based on the categorization of self efficacy questionnaire (high, medium, and low) to be interviewed. A qualitative approach with a descriptive form was used with the aim of describing the ability of mathematical computational thinking in terms of self efficacy in class VIII students at SMPN 226 Jakarta. Data were collected from questionnaires, written description tests, and interview guidelines, then analyzed through data reduction, data presentation and conclusion drawing. The results showed that students in the high self efficacy category met four indicators, namely, decomposition, pattern recognition, abstraction, and algorithmic thinking. Students with moderate self efficacy fulfill three indicators, namely, decomposition, pattern recognition, and abstraction. Meanwhile, students with low self efficacy fulfill two indicators namely, decomposition, and pattern recognition. In addition, the results of this study indicate that the better the self efficacy in students, the better the mathematical computational thinking ability. Keywords: Mathematical Computational Thinking Ability, Self Efficacy